PENGARUH SERVANT LEADERSHIP, PERCEIVED ORGANIZATIONAL SUPPORT, DAN WELL-BEING TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA GURU SMK MUDITA KOTA SINGKAWANG [THE EFFECT OF SERVANT LEADERSHIP, PERCEIVED ORGANIZATIONAL SUPPORT, AND WELL-BEING ON THE ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF TEACHER AT MUDITA VOCATIONAL SCHOOL SINGKAWANG CITY] - Hin Su Khian; Inocentius Bernarto (Polyglot, 2021)
Education is one of the formal organizations that serves to increase students' knowledge, it is also a place to obtain various knowledge as provisions for the future.The purpose of this research was to determine the effect of servant leadership, organizational citizenship behavior OCB, Perceived Organizational Support (POS), well-being on the Organizational Citizenship Behavior (OCB). The research subjects are 39 teachers teaching in SMK Mudita Vocational School, in which Organizational Citizenship Behavior (OCB) was identified. The research design in the of path analysis with a cumulative approach. The applied method is in SmartPL 32 program. The research instrument is through distributing questionnaire and by interviewing the principal and teachers of SMK Mudita Vocational School in Singkawang City. The sampling technique used is by gathering data from the entire population. This technique as census, the results   research shows that: servant leadership positively influences Organizational Citizenship Behavior (OCB), Perceived Organizational Support positively affects Organizational Citizenship Behavior (OCB) Well-being positively affects Organizational Citizenship Behavior (OCB) positively.BAHASA INDONESIA ABSTRACT: Pendidikan merupakan salah satu organisasi formal yang berfungsi untuk meningkatkan pengetahuan siswa, juga merupakan tempat untuk memperoleh berbagai ilmu pengetahuan sebagai bekal untuk dikemudian hari. Tujuan penelitian ini untuk mengetahui Pengaruh servant leadership, organizational citizenship behavior OCB, Perceived Organizational Support (POS) ,Well-Being terhadap terhadap Organizational Citizenship Behavior (OCB) guru pada sekolah SMK Mudita dikota Singkawang. Adapun subjek penelitian adalah 39 guru yang mengajar di sebuah Sekolah SMK Swasta di kota singkawang, dimana teridentifikasi Organizational Citizenship Behavior (OCB) didalamnya.mengunakan desain penelitian adalah Desain penelitian analisis jalur dengan cara pendekatan kumulatif. Metode yang digunakan dalam program SmartPL32. Istrumen penelitian adalah membagi kuesioner dan wawancara kepala sekolah dan guru SMK Mudita Kota Singkawang.Teknik sampel yang digunakan dalam pengambil data dari keseluruhan jumlah populasi. Teknik ini disebut sensus, Hasil dari penelitian ini menunjukan bahwa Servant Leadership mempengaruhi Organizational Citizenship Behavior (OCB) secara positif, Perceived Organizational Support mempengaruhi Organizational Citizenship Behavior(OCB) secara positif, Well-being mempengaruhi Organizational Citizenship Behavior (OCB) secara positif.